A comprehensive analysis concerning eating behavior associated with chronic diseases among Romanian community nurses - Lidia-Manuela Onofrei; Maria Puiu; Maria Puiu; Adela Chirita-Emandi; Adela Chirita-Emandi; Costela Lacrimioara Serban; Costela Lacrimioara Serban; Costela Lacrimioara Serban (Frontiers Media S.A., 2024)
IntroductionLifestyle factors, including inadequate eating patterns, emerge as a critical determinant of chronic disease. Apart from caring for patients, nurses should also take an active role in monitoring and managing their own health. Understanding the intricate relationship between nurses' eating behavior and managing their own health is crucial for fostering a holistic approach to healthcare, therefore our study aimed to evaluate eating behavior and demographic factors influencing chronic disease prevalence in a sample of community nurses from Romania.MethodsBetween October-November 2023, 1920 community nurses were invited to answer an online survey, using an advertisement in their professional network. Of them, 788 responded. In the survey, which included a semi-quantitative food frequency questionnaire with 53 food items, the Intuitive Eating Survey 2 (IES-2), and demographic items were used.ResultsA multivariate model was built for the prediction of the association between eating behavior and other factors associated with chronic diseases. The majority of participants were females (95.1%), with the largest age group falling between 40 and 49.9 years (48.2%). Regarding the EFSA criteria for adequate carbohydrate and fat intake, 20.2% of the group have a high intake of carbohydrates, respectively, 43.4% of the group have a high intake of fat. Analysis of chronic diseases indicated that 24.9% of individuals reported at least one diagnosis by a physician. The presence of chronic disease was associated with a low level of perceived health status, with an OR = 3.388, 95%CI (1.684-6.814), compared to those reporting excellent or very good perceived health status. High stress had an OR = 1.483, 95%CI (1.033-2.129). BMI had an OR = 1.069, 95%CI (1.032-1.108), while low carbohydrate diet score had an OR = 0.956, 95%CI (0.920-0.992). Gender and IES-2 did not significantly contribute to the model, but their effect was controlled.DiscussionBy unraveling the intricate interplay between nutrition, lifestyle, and health outcomes in this healthcare cohort, our findings contribute valuable insights for the development of targeted interventions and support programs tailored to enhance the well-being of community nurses and, by extension, the patients they support.